Modeling and optimizing a polycaprolactone/gelatin/polydimethylsiloxane nanofiber scaffold for tissue engineering: using response surface methodology. Issue 3 (4th March 2021) - Dehghan, Mahdieh; Mehrizi, Mohammad Khajeh; Nikukar, Habib
Abstract: Patients suffering from diseased or injured parts of their body could be treated with transplanted tissue, organ, or parts of them; however, there is a severe shortage of allogeneic engrafts that is worsening annually. In the field of tissue engineering and medical rehabilitation, scientists apply the principles of cellular transplantation, material science, and environmental engineering to build biological substitutes that rehabilitate and maintain part of normal function in injured and damaged tissues. In this study, the production process of a biocompatible scaffold made from polycaprolactone/gelatin/polydimethylsiloxane (PCL/GEL/PDMS) and its optimization using response surface methodology (RSM) method has been reported. The PCL/GEL/PDMS blend ratio, their interactions and their solubility were investigated on the mechanical properties, biodegradability, and biocompatibility of nanofibers. These variables have a quadratic relationship with the PCL/GEL/PDMS blend ratio. With the experimental design, PCL/GEL/PDMS optimization scaffold was fabricated as a scaffold for tissue engineering. These results indicate that the PCL/GEL/PDMS scaffold is a novel biocompatible scaffold, suitable for tissue engineering.